2017
DOI: 10.1155/2017/9531964
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Metabolic Syndrome in Central and South American Immigrant Residents of the Washington, DC, Area

Abstract: The objective of this study was to estimate the prevalence of Metabolic Syndrome (MetS) and its risk components and then compare differences in the risk components among low-income, uninsured Central and South American recent immigrants to the USA. This cross-sectional survey sampled 1,042 adult patients from a medical clinic in metropolitan Washington, DC. The overall prevalence of the MetS was 26.9% estimated using the modified harmonized definition. The most common abnormal metabolic indicator for women was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Population based studies have demonstrated differences in prevalence by gender and ethnicity for hypercholesterolemia and MetS [17,18]. A recent survey conducted by National Center for Health Statistics reported that during 2015–2016, 12.4% of adults had high Tchol and 18.4% had low HDL-C [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population based studies have demonstrated differences in prevalence by gender and ethnicity for hypercholesterolemia and MetS [17,18]. A recent survey conducted by National Center for Health Statistics reported that during 2015–2016, 12.4% of adults had high Tchol and 18.4% had low HDL-C [17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence of MetS among Lebanese adults aged 18–65 years old was shown to be ~31% with men presenting with a higher rate than women [19]. Going in the same direction, findings from the National Health and Nutrition Examination Survey reported that the prevalence of MetS among the US adult population was 34.0% [18]. While the prevalence of MetS was comparable between the two genders (men (35%) and women (33%)) in the US, it was higher among men in Lebanon.…”
Section: Discussionmentioning
confidence: 99%
“…Sindroma metabolik merupakan kumpulan kelainan metabolik yang berhubungan dengan peningkatan resiko terjadinya penyakit kardiovaskular dan diabetes tipe 2 (IDF, 2006;Gill et al, 2017). Hingga saat ini, kriteria sindroma metabolik masih beragam mulai dari International Diabetes Federation (IDF), WHO, The National Cholesterol Education Program Adult Treatment Planner III (NCEP ATP III) dan lainnya.…”
Section: Pendahuluanunclassified
“…Results of previous studies have shown high prevalence of MS in both Western and Asian countries (7)(8)(9)(10). For example, the prevalence of MS was reported to be 32.3%, 33%, and 28.3% in England, India, and Saudi Arabia, respectively (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%